PSIKOTERAPI SUFISTIK TELA’AH ATAS DIMENSI PSIKOLOGI DAN KESEHATAN MENTAL DALAM SUFISME - Khairunnas Rajab (Ta'dib, 2008)
Islamic psychospiritual is a psychology framework which seeks Islamic values related directly to human psyche. This study emphasizes more on tasawwuf since the spiritual values with an intuitive approach is more coherent and similar to the dimension of psychology. Suffism itself is tadzkiyyah al-nafs method by which happiness, peacefulness, and mental health can be obtained.Kata Kunci: kesehatan mental, tadzkiyyah al-nafs, sufisme, psikologi, dan maqam al-ahwal